PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA SEKRETARIAT DAERAH KOTA TOMOHON - Plangiten, Novva Novita (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: Leadership Leadership Organization is a major factor and the first that affect an employeejob satisfaction. The better the leadership of the head of the Organization will be higher the jobsatisfaction felt by employeesThis study will use the survey method with quantitative approach using simple correlation andregression analysis.The magnitude of the effect of variable work motivation on employee job satisfaction variablesindicate that the coefficient of determination of 0.4436 (44.36%). This means that the variable of workmotivation significant effect on job satisfaction of 44.36%. Referring to the results of this study providethe sense that the efforts made by the leadership associated with the level of job satisfaction ofemployees already on the path to truth.Keywords: Leadership, Work Motivation and Job Satisfaction